How consumers’ attitude towards chatbots affects their experience and behavioural intentions: The case of South Africa - Saah, Paul; Mbohwa, Charles; Madonsela, Nelson Sizwe (Asian Development Policy Review, 2024)
The purpose of this study is to determine how consumers’ attitudes towards chatbots affect their experiences and behavioural intentions. In the contemporary business environment, a lot of enterprises and outstanding brands have resorted to using modern technology in their business operations, such as chatbots, to offer 24-hour customer care. The quantitative research approach was adopted for this study with a correlational survey model to collect and analyse numerical data to ascertain how consumers’ attitudes towards chatbots affect their experiences and behavioural intentions. The population of this study comprises customers of renowned brands in South Africa. The sample size was 211 consumers with at least five years’ experience of using chatbots in South Africa who were selected using a nonprobability convenience sampling method. The Statistical Package for Social Sciences (SPSS) and SmartPLS3 were used to analyse the data. The study’s findings show a strong predictive correlation between customer contacts and behavioural intent towards chatbots and perceived usefulness, ease of use, enjoyment, and seeming risk. The significance of these aspects in influencing customer attitudes and behaviours while interacting with chatbot technologies is highlighted by these findings. Understanding and optimizing perceived usefulness, ease of use, fun, and apparent risk in chatbot design is crucial for shaping positive consumer interactions and influencing behavioral intent towards chatbots. Therefore, it is highly recommended that renowned brands and companies looking to optimise their chatbot systems endeavour to improve customer experiences and encourage long-term behavioural intentions among South African users.